Glycolysis-derived acidic microenvironment as a driver of endothelial dysfunction in systemic sclerosis. (26th January 2021) - Andreucci, Elena; Margheri, Francesca; Peppicelli, Silvia; Bianchini, Francesca; Ruzzolini, Jessica; Laurenzana, Anna; Fibbi, Gabriella; Bruni, Cosimo; Bellando-Randone, Silvia; Guiducci, Serena; Romano, Eloisa; Manetti, Mirko; et al.
Abstract: Objectives: SSc is an autoimmune disease characterized by peripheral vasculopathy and skin and internal organ fibrosis. Accumulating evidence underlines a close association between a metabolic reprogramming of activated fibroblasts and fibrosis. This prompted us to determine the metabolism of SSc dermal fibroblasts and the effect on the vasculopathy characterizing the disease. Methods: A Seahorse XF96 Extracellular Flux Analyzer was used to evaluate SSc fibroblast metabolism. In vitro invasion and capillary morphogenesis assays were used to determine the angiogenic ability of endothelial cells (ECs). Immunofluorescence, flow cytometry and real-time PCR techniques provided evidence of the molecular mechanism behind the impaired vascularization that characterizes SSc patients. Results: SSc fibroblasts, compared with controls, showed a boosted glycolytic metabolism with increased lactic acid release and subsequent extracellular acidification that in turn was found to impair EC invasion and organization in capillary-like networks without altering cell viability. A molecular link between extracellular acidosis and endothelial dysfunction was identified as acidic ECs upregulated MMP-12, which cleaves and inactivates urokinase-type plasminogen activator receptor, impairing angiogenesis in SSc. Moreover, the acidic environment was found to induce the loss of endothelial markers and the acquisition of mesenchymal-like features in ECs, thus promoting the endothelial-to-mesenchymal transition process that contributes to both capillary rarefaction and tissue fibrosis in SSc. Conclusion: This study showed the relationship of the metabolic reprogramming of SSc dermal fibroblasts, extracellular acidosis and endothelial dysfunction that may contribute to the impairment and loss of peripheral capillary networks in SSc disease.